Nanotechnology-driven advances in intranasal vaccine delivery systems against infectious diseases - Zhang, Zhihan; Yang, Yumeng; Huang, Liwen; Yuan, Lei; Huang, Sijian; Zeng, Zihang; Cao, Yuan; Wei, Xianghong; Wang, Xiaomei; Shi, Mingsong; Zhong, Maohua (Frontiers in Immunology, 2025)
Outbreaks of emerging and re-emerging infectious diseases have consistently threatened human health. Since vaccinations are a powerful tool for preventing infectious illnesses, developing new vaccines is essential. Compared to traditional injectable vaccines, mucosal vaccines have the potential to offer more effective immune protection at mucosal sites. Mucosal immunization strategies include sublingual, oral, intranasal, genital, and rectal routes, in which intranasal immunization being the most efficient and applicable method for mucosal vaccine delivery. Nevertheless, low antigen availability and weak immunogenicity making it challenging to elicit a potent immune response when administered intranasally, necessitating the incorporation of immune delivery systems. However, there is a notable absence of reviews that summarize the intranasal vaccine delivery system against infectious disease. Therefore, this review summarizes the recent advances in intranasal delivery systems, classified by physical and chemical properties, and proposes potential improvement strategies for clinical translation. This review elucidates the potential and current status of intranasal delivery systems, while also serving as a reference point for the future development of intranasal vaccines.